Synthesis and Characterization of La-Doped Luminescent Multilayer Films. (22nd January 2017) - Wang, Tianlei; Liu, Meitang; Ma, Hongwen; Cao, Defu
Abstract : In this work, we have successfully designed ordered luminescent multilayer films based on La-doped nonmagnetic or magnetic inorganic nanostructure with electronic microenvironment (EM). The inorganic nanosheets with opposite charge can assemble EM between the interlayers. At the same time, their elements on nanosheets of layer double hydroxides (LDHs) are facile to be replaced so that we can introduce transition metal or lanthanide elements. Besides, ferromagnetic effect (FE) can be formed in this microenvironment due to introducing transition metal on LDHs nanosheets. As a result, we confirm that EM, FE, and doping La element in the LDHs can affect the vibration of backbone of chromophores and then prolong the luminescent lifetime, which suggests a new pathway for developing the novel light-emitting thin films.